2019
DOI: 10.1016/j.disc.2019.111614
|View full text |Cite
|
Sign up to set email alerts
|

Boolean constant degree functions on the slice are juntas

Abstract: We show that a Boolean degree d function on the slice [n] k = {(x 1 , . . . , x n ) ∈ {0, 1} : n i=1 x i = k} is a junta, assuming that k, n − k are large enough. This generalizes a classical result of Nisan and Szegedy on the hypercube. Moreover, we show that the maximum number of coordinates that a Boolean degree d function can depend on is the same on the slice and the hypercube.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 10 publications
2
33
0
Order By: Relevance
“…Finally, with a little more representation theory effort, we are able to derive from Theorem 1.1 a Nisan-Szegedy Theorem for the multislice (cf. [48]), which is (roughly) an = 0 version of the Friedgut Junta Theorem; this generalizes previous work on the Hamming slice [25]. It says that if A ⊆ U κ is of "degree k" -meaning that its indicator function can be written as a linear combination of k-junta functions -then A must be an exp(O(k))-junta itself.…”
Section: Applicationssupporting
confidence: 62%
“…Finally, with a little more representation theory effort, we are able to derive from Theorem 1.1 a Nisan-Szegedy Theorem for the multislice (cf. [48]), which is (roughly) an = 0 version of the Friedgut Junta Theorem; this generalizes previous work on the Hamming slice [25]. It says that if A ⊆ U κ is of "degree k" -meaning that its indicator function can be written as a linear combination of k-junta functions -then A must be an exp(O(k))-junta itself.…”
Section: Applicationssupporting
confidence: 62%
“…Classical results in analysis of Boolean functions on the hypercube show that Ω(2 d ) ≤ γ d (H(n, 2)) ≤ d2 d−1 . In ongoing work [28], we have shown that for k, n − k ≥ exp(d) it holds that γ d (J(n, k)) = γ d (H(n, 2)), and we suspect that a similar result holds for the multislice. More generally, we conjecture that in the domains considered in the paper, Boolean degree d functions can be formed by combining a bounded number of Boolean degree 1 functions.…”
Section: Future Workmentioning
confidence: 83%
“…[FI18] recently considered an analog of the parameter R(f ) for the family of level k slice functions which are Boolean functions whose domain is restricted to the set of inputs of Hamming weight exactly k. They showed that, provided that min(k, n−k) is sufficiently large (at least B d for some fixed constant B) then every level k slice function on n-variables of degree at most d depends on at most R d variables. (See [FI18] for precise definitions and details.) Thus our improved upper bound on R d applies also to the number of relevant variables of slice functions.…”
Section: Introductionmentioning
confidence: 99%